1983
DOI: 10.1111/j.1748-1716.1983.tb07202.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of acetazolamide on cerbral blood flow in man

Abstract: We have followed the time course of the effect of the carbonic anhydrase inhibitor acetazolamide injected i.v. in unanesthetized healthy human beings. The dose administered was 500 mg as a bolus. Cerebral blood flow (CBF) was measured continuously before, during and after the injection, using a pulsed ultrasound doppler system, which measured the instantaneous mean velocity across the lumen of the internal carotid artery, just below its entrance into the skull. Ventilation, heart-rate, end-expiratory PCO2, art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2
3

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(82 citation statements)
references
References 24 publications
5
72
2
3
Order By: Relevance
“…Such a detailed assessment of the time course of CBF changes is difficult with the use of methods requiring administration of exogenous contrast agents or radiotracers. Doppler ultrasonography 17,18 and phase-contrast MR imaging 19 have been used to assess the time course of cerebrovascular response to ACZ and have shown temporal changes in blood flow or velocity in the major cerebral arteries that are consistent with temporal changes in rCBF observed in the current study. Planar dynamic imaging after radio-labeled albumin has also revealed similar temporal patterns in alterations of cerebral blood volume representing intravascular volume.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Such a detailed assessment of the time course of CBF changes is difficult with the use of methods requiring administration of exogenous contrast agents or radiotracers. Doppler ultrasonography 17,18 and phase-contrast MR imaging 19 have been used to assess the time course of cerebrovascular response to ACZ and have shown temporal changes in blood flow or velocity in the major cerebral arteries that are consistent with temporal changes in rCBF observed in the current study. Planar dynamic imaging after radio-labeled albumin has also revealed similar temporal patterns in alterations of cerebral blood volume representing intravascular volume.…”
Section: Discussionsupporting
confidence: 80%
“…2,13 Previous studies with the use of Doppler ultrasonography demonstrated increased blood velocity after ACZ injection in the MCA 17 and internal carotid artery. 18 The administration of ACZ may shorten the arrival time as a result of increased blood velocity and aid early influx of labeled water into the brain tissues, which may enhance ASL signals with a short PLD preferentially and consequently cause overestimation of CVR. The mean CVR values reported in normal subjects range from 25-31% with the use of 133 Xe inhalation SPECT, 18,21-23 from 33.5-35% with the use of 15 O-water positron-emission tomography, 24,25 and from 37.7-54.2% with the use of ASL MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Intravenous doses of 7 to 30 mg/kg ACZ in rats 1,5 and 0.5 to 1 g in humans [2][3][4]6 produce no or little change in blood pressure and an increase in cerebral blood flow (CBF), so that cerebral vascular resistance (CVR) decreases. In clinical investigation, this decrease in CVR in response to ACZ injection is often considered a surrogate of the decrease in CVR elicited by hypotension (ie, autoregulatory vasodilation).…”
mentioning
confidence: 99%
“…The range of values usually obtained in a series of ten from one baby was much greater than we would expect as normal physiological variation (see Table 2 and Cross et al 1979). Continuous ultrasound recording of blood velocities in the internal carotid arteries in adults gives rather stable values (Hauge, Thoresen & Wall0e, 1980;Hauge, Nicolaysen & Thoresen, 1982).…”
Section: Resultsmentioning
confidence: 98%